CRYSTAL CHEMISTRY OF OWYHEEITE: NEW DATA - Mozgova N.; Bortnikov N.; Moëlo Y.; Picot P.; Vrublevskaya Z. (My University, 1983)
Comparative electron microprobe study of owyheeite from thirteen ore deposits shows significant variations in the concentration of major elements. These can be correlated with the chemical composition of the associated sulfosalts. Sometimes, some minor elements may be present: Cu and As (very frequent), Sn and Bi (less frequent), Tl and Se (exceptional). Considering certain substitution rules for minor elements, the analyses plotted in the Pb2S2−Ag2S−Sb2S3 system show a limited solid-solution field, the elongation of which follows the substitution 2 Pb2+⇌Ag++Sb3+. This solid-solution field includes the composition of the variety “teremkovite”, but excludes the initial formula for owyheeite proposed byShannon. The formula Pb10−2xSb11+xAg3+xS28 (−0.13≤x≤+0.20) describes compositional variation of members with the highest Ag/Sb ratio; a more general formula would require the determination of the crystal structure. No individual minor element appears to be responsible for stabilizing owyheeite. The stabilization may be due to a combined effect of two elements, such as Cu and Sn. Electron diffraction patterns show superstructure reflections which are related to the (Ag+Cu) concentration, as well as to the scale of the complex twinning characteristic of owyheeite.